2012
DOI: 10.1262/jrd.11-133h
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Hyperbaric Oxygen Therapy on the Follicular Survival in the Mouse Ovary after Transplantation

Abstract: Abstract.A large proportion of follicles are lost during the initial ischemia that occurs after transplantation of ovarian tissues. Thus, the effect of hyperbaric oxygen therapy (HBO) on the follicular loss of ovarian tissues after transplantation was examined in mice. Ovarian slices from ICR mice were transplanted under the kidney capsule in ovariectomized ICR. Hyperbaric oxygen with 100% oxygen was initiated for 30 min at 2.5 atmospheres absolute immediately after transplantation, and this treatment was repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Experimentally, HBO was found significantly effective in the survival of transplanted cells or tissues like liver, bone, thyroid, pancreatic islet cells [ 13 ]. Although a large proportion of ovarian follicles were lost during the initial ischemia after transplantation of ovaries, recently it was also found that HBO was also beneficial for the follicular survival of the transplanted mouse ovaries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, HBO was found significantly effective in the survival of transplanted cells or tissues like liver, bone, thyroid, pancreatic islet cells [ 13 ]. Although a large proportion of ovarian follicles were lost during the initial ischemia after transplantation of ovaries, recently it was also found that HBO was also beneficial for the follicular survival of the transplanted mouse ovaries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have suggested that damage of cryopreserved ovarian grafts might be induced by initial ischemia and/or ischemic perfusion injury rather than from vitrification-associated processes [30][31][32][33][34][35][36][37][38]. Several attempts have been made to prevent the follicular loss of cryopreserved ovarian tissues after transplantation [14,15,[38][39][40][41][42][43]. In the dog, the effect of desialylated erythropoietin on the follicular survival of vitrified ovaries after xenotransplantation has been reported [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed revascularization and ischemia appear to be responsible for follicular loss and apoptosis [ 96 , 97 , 98 ]. Administration of desialylated erythropoietin [ 94 , 99 , 100 ], erythropoietin [ 97 ], or hyperoxygen therapy [ 101 ] is effective in suppressing follicular loss after ovarian transplantation in dogs. Vitrification is more suitable than slow freezing for cryopreserving canine ovarian tissues [ 93 , 94 , 95 , 96 , 99 , 100 , 102 , 103 , 104 , 105 ].…”
Section: Cryopreservation Of Gonadal Tissuesmentioning
confidence: 99%